Cyanogenic Glucosides and Derivatives in Almond and Sweet Cherry Flower Buds from Dormancy to Flowering - Del Cueto, Jorge; Ionescu, Irina A.; Pičmanová, Martina; Gericke, Oliver; Motawia, Mohammed S.; Olsen, Carl E.; Campoy, José A.; Dicenta, Federico; Møller, Birger L.; Sánchez-Pérez, Raquel (Frontiers in Plant Science, 2017)
Almond and sweet cherry are two economically important species of the Prunus genus. They both produce the cyanogenic glucosides prunasin and amygdalin. As part of a two-component defense system, prunasin and amygdalin release toxic hydrogen cyanide upon cell disruption. In this study, we investigated the potential role of prunasin and amygdalin and some of its derivatives in endodormancy release of these two Prunus species. The content of prunasin and of endogenous prunasin turnover products in the course of flower development/opening was examined in five almond cultivars – differing from very early to extra-late in flowering time – and in one sweet early cherry cultivar. In all cultivars, prunasin began to accumulate in the flower buds shortly after dormancy release and the levels dropped again just before flowering time. In almond and sweet cherry, the turnover of prunasin coincided with increased levels of prunasin amide whereas prunasin anitrile pentoside and beta-D-glucose-1-benzoate were abundant in almond and cherry flower buds at certain developmental stages. These findings indicate a role for the turnover of cyanogenic glucosides in controlling flower development/opening in Prunus species.